Implementasi Program padat Karya sebagai Upaya Pemberdayaan Masyarakat di Kampung Batik Tin Gundih - Ananda, Yuan Friska; Susi Hardjati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The high unemployment rate in Surabaya has prompted the municipal government to initiate the Padat Karya program as a solution to improve community welfare. One of the implementations of this program is the establishment of Kampung Batik Tin Gundih in Bubutan District. This study aims to analyze community empowerment through the Padat Karya Program in Kampung Batik Tin Gundih, Bubutan District, Surabaya. This program is an initiative of the City Government to address unemployment and poverty through the creation of jobs based on local potential. The research uses a descriptive qualitative approach with techniques such as interviews, observations, and documentation. The theory used refers to Wilson's empowerment model, which includes four stages: awareness, understanding, utilization, and habit formation. The research findings indicate that all stages have been implemented: residents were made aware of local potential, batik-making training was conducted, batik production is ongoing, and batik-making activities have become part of daily life. However, challenges such as weak management, uneven incentives, and unequal participation remain obstacles. The conclusion of this study indicates that the Labor-Intensive Program is capable of empowering residents economically and socially, although improvements are needed in program management and sustainability. Recommendations are made for the government to strengthen institutional frameworks, stabilize incentives, and provide ongoing support to create equitable and sustainable transformation.